Factors Affecting the Adoption of Good Agricultural Practices (GAP) Among Smallholder Vegetable Farmers in Surkhet District, Nepal - Rijal, Saroj; Singh, Om Prakash; Pandeya, Shreesha; Bhatta, Sushmita; Sapkota, Smriti; Mishra, Binayak Prakash (Journal of Agriculture and Forestry University, 2025)
A study was conducted in 2022 within Birendranagar municipality of Surkhet District of Nepal to identify the factors affecting the adoption of Good Agricultural Practices (GAP) among smallholder vegetable farmers. Employing a random sampling approach, 115 smallholder vegetable farming households were selected. Primary data were gathered through semistructured questionnaires administered to household heads. The collected data was analyzed using a binary probit model. The findings revealed formal education, farming experience, training program, agricultural extension services, membership in agricultural cooperatives, annual household income, agricultural subsidies, and reliance on farming as the primary source of income were found significantly influencing the adoption of GAP. Thus, it is essential to provide smallholder vegetable farmers with regular extension services and trainings on GAP to promote its adoption. Further, agricultural cooperatives should be strengthened, subsidies should be made accessible to smallholder farmers and households that rely solely on agriculture for their livelihood should be prioritized to promote efficient adoption of GAP.